The end of cheap talk about poverty reduction: The cost of closing the poverty gap while maintaining work incentives - Diego Collado; Béa Cantillon; Karel Van den Bosch; Tim Goedemé; Dieter Vandelannoote (University of Essex, Institute for Social and Economic Research (ISER), 2017)
How can poverty reduction be improved and at what cost? Available evidence suggests that social investment strategies and employment policies are important but not sufficient. In order to reduce the number of people below the relative at-risk-of-poverty threshold of the EU, countries must develop not only effective employment policies but also ensure adequate social protection. This implies increasing social transfers for working and nonworking households, while protecting work incentives. In this paper we show that this is not a cheap option. We calculate the hypothetical cost of closing the poverty gap while maintaining the existing average labour market participation incentives at the bottom of the income distribution. We do it in three of the most developed welfares states of the EU, representing different welfare regimes, namely Belgium, Denmark and the United Kingdom. Results show that this would require around two times the budget needed to just lift all disposable household incomes to the poverty threshold. The cost would obviously be lower in countries with smaller poverty gaps and with weaker participation incentives. Furthermore, the results suggest that for anti-poverty strategies to be effective other factors should be considered more carefully, including the drivers of rising inequalities in market incomes, and especially the downward pressures on low wages, as well as the most appropriate magnitude of financial work incentives.
Keywords: H23; H24; H53; I32; I38; 330; poverty gap; work incentives; redistribution; tax-benefit system; minimum income; in-work benefit